2022
DOI: 10.47750/pnr.2022.13.s06.339
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Risk Assessment of Indian Pulse processing firms using FMEA Techniques – Evidence from selected states of India

Abstract: The pulse value chain played significant role in agriculture and other industry sector such as food , pharma industry. The pulse value chain consists of sequences of business activities that perform significant activities, from primary production transformation into the final product to marketing for final consumption to the consumer. Pulse value chain develops different framework structures for developing competitive business strategy development to identify the significant constraints in a compressive manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Pareto analysis was done in Microsoft excel. Sah and Arora (2022) also used Pareto analysis to generate line chart has been determined through the Pareto analysis of potential critical operational risk, and demand risk analyses to define the severity of risk factors [6]. 2021) revealed that the labour employment was higher in case of Integrated Farming system (IFS) as many components were to be maintained as compared to non-IFS system [11].…”
Section: Methodsmentioning
confidence: 99%
“…Pareto analysis was done in Microsoft excel. Sah and Arora (2022) also used Pareto analysis to generate line chart has been determined through the Pareto analysis of potential critical operational risk, and demand risk analyses to define the severity of risk factors [6]. 2021) revealed that the labour employment was higher in case of Integrated Farming system (IFS) as many components were to be maintained as compared to non-IFS system [11].…”
Section: Methodsmentioning
confidence: 99%